PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PASIEN MEDICAL CHECK UP (MCU) PADA RUMAH SAKIT DR. AK. GANI PALEMBANG - Elisa Elisa; Divianto Divianto; Manuel Hutagaol (Politeknik Negeri Sriwijaya, 2014)
This final report titled “The impact of the service quality toward the patient satisfaction of medical check-up at RS. DR. AK. GANI Palembang”. The objective of this research is to know the level of patient satisfaction toward the service quality which is given and to know which service quality variable that most significantly influence the patient satisfaction. In analyzing the problems, the writer used interview technique and quesionnaires by distributing questionnaires to every patients who conducted medical check-up with 60 questionnaires that is distributed. In processing the data, the writer used SPSS version 20.0 program. The results showed that the reliability variable and the responsiveness variable had strong influence toward the patient satisfaction and the strongest one was the reliability dimension with 43,4%.